2000
DOI: 10.1243/0957650001538308
|View full text |Cite
|
Sign up to set email alerts
|

Water spray cooling of gas turbine cycles

Abstract: Aeroderivative gas turbines intercooled by water spray injection systems have recently entered service. A calculation framework is presented which permits the effect of water spray injection for both intercooling and inlet chilling to be evaluated and compared with conventional cooling techniques for a range of cycles. The calculations are based on representative performance maps for compressors and turbines, focusing upon the actual performance benefits that can be realized from existing turbomachinery. The p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…The pressure ratio for the cycle is defined as (24) In general, the thermal efficiency of the cycle may be determined from (25) The second-law analysis is a powerful tool in the design, optimization, and performance evaluation of energy systems. The general principles and methodology of second-law analysis may be found in Moran [27], Bejan [28], and Gaggioli [29].…”
Section: The First and Second-law Analysis Of The Cyclementioning
confidence: 99%
See 1 more Smart Citation
“…The pressure ratio for the cycle is defined as (24) In general, the thermal efficiency of the cycle may be determined from (25) The second-law analysis is a powerful tool in the design, optimization, and performance evaluation of energy systems. The general principles and methodology of second-law analysis may be found in Moran [27], Bejan [28], and Gaggioli [29].…”
Section: The First and Second-law Analysis Of The Cyclementioning
confidence: 99%
“…al. [24] reported that spray intercooling can give a greater power boost than conventional intercooling for a given compressor operating envelope and spray inlet chilling can give performance benefits comparable with absorption chilling.…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have shown that the spray evaporation cooling process can be analyzed by numerical simulation. Ritchey et al [4] constructed a numerical simulation calculation framework for the inlet spray cooling technology. Within a given range of compressor operation, spray intermediate cooling can provide greater power gain than traditional intermediate cooling, and spray inlet cooling can provide performance advantages comparable to those of absorption refrigeration cooling.…”
Section: Introductionmentioning
confidence: 99%
“…Examples of the work include spray cooling in gas turbines [4,5], spray applications in incineration processes [6], fire fighting [7], spray forming [8,9] and spray drying [1,2]. However, there is sparse CFD modelling investigation dealing with spray cooling of the hot gas.…”
Section: Introductionmentioning
confidence: 99%